ANALYSIS OF THE POTENTIAL OF WIND ENERGY IN THE PUGER COAST OF THE THREE BLADES DARRIEUS WIND TURBINE PERFORMANCE - Yushardi Yushardi; Sudarti Sudarti; Melisa Putri Febriyanti (Indonesian Journal of Multidisciplinary Science, 2022)
Wind energy is one of the renewable energy sources that can still be explored today. The advantage obtained by utilizing wind energy is that the energy source is easy to obtain because it comes from nature. The form of utilization of wind energy in the form of wind power plants is one of the alternative technologies as an effort to meet the increasing electricity needs of the community, especially in coastal areas. Therefore, to advance this abilityl, A tool that transforms wind energy into electrical energy, such as a wind turbine, is requsite. This analysis aims to survey and assess the wind energy potential of the three blade wind turbine off the coast of Puger. The research uses research methods Research and Information Collection method and data collection techniques with needs analysis and Systematic Literature Review (SLR) by utilizing relevant and valid library sources. In the results of the study, the vertical axis wind turbine with 3 blades produces the highest rotor rotation of 224.65 rpm at a speed of wind of 4,2 m/s, as well as a maximum wind power of 3.50 watts as well as a maximum generator power of 2.28 watts at a maximum speed of 2.28 watts. maximum wind 6 m/s. Therefore, this 3-blade Darrieus wind turbine is in accordance with the wind potential that exists on the Puger coast.